تقاسيم الربح والخسارة في عقد المضاربة و تطبيقاته في بعض البنوك الإسلامية في ماليزيا : دراسة تحليلية - أديلاني، عبد الكبير بللو (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2009)
This thesis focuses on sharing of profit and loss in Mudarabah savings and investment account and its implementation in some Islamic banks in Malaysia. It is an effective way of modern implementation of Mudarabah contract of Shari'ah in the Islamic banks. At the beginning of the thesis the researcher has discussed the meaning of “profit and loss” in Islamic banks and its standard in Shari'ah, and the meaning of Mudarabah in concept of Shari'ah, its pillars and conditions. This study provides an opportunity to ensure and guarantee accounts in Islamic banks and jurisprudence adjustment for them, and deposits insurance. This research has discussed practical of modern Mudarabah in Islamic banks, in addition, he discussed the quantification of the profit-sharing, and abdication of profit by “Mudarib or Rabbul Mal”. Also, lease combining and profit participation and issue of guarantee of capital and profit. The researcher has chosen Bank Islam Malaysia Berhad as a model, and compared with Bank Muamalat Malaysia Berhad in the way of sharing of profit in both banks. And the researcher compared between Islamic banks and conventional banks in terms of sharing of profit. The researcher has utilized the inductive method in order to gather information from the sources and analytical and comparative methods in order to analyze the views of scholars concerning the study and compared their views.